2019
DOI: 10.1002/jsfa.9739
|View full text |Cite
|
Sign up to set email alerts
|

Furan formation from ingredient interactions and furan mitigation by sugar alcohols and antioxidants of bamboo leaves in milk beverage model systems

Abstract: BACKGROUND Furan is a potential carcinogen that can be formed in various heat‐treated foods, including milk beverages. Studies on the formation and mitigation of furan in milk beverages are rare. In the present study, the effects of ingredients on furan formation and the reduction of furan by sugar alcohols and antioxidants of bamboo leaves (AOB) were investigated in a milk beverage model system. RESULTS The results obtained demonstrated that the Maillard reaction is the major pathway for furan formation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, partial substitution with sorbitol may favor furan mitigation (Anese & Suman, 2013). Another study performed in the milk beverage system also reported that complete substitution of high-fructose corn syrup or sucrose with sugar alcohols (xylitol, sorbitol, and mannitol) resulted in a significant reduction (65.1%−88.6%) in furan yields, with xylitol showing the highest inhibitory effect (Guo et al, 2019).…”
Section: Methods To Mitigate Furan In Foodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, partial substitution with sorbitol may favor furan mitigation (Anese & Suman, 2013). Another study performed in the milk beverage system also reported that complete substitution of high-fructose corn syrup or sucrose with sugar alcohols (xylitol, sorbitol, and mannitol) resulted in a significant reduction (65.1%−88.6%) in furan yields, with xylitol showing the highest inhibitory effect (Guo et al, 2019).…”
Section: Methods To Mitigate Furan In Foodsmentioning
confidence: 98%
“…The second pathway through the Maillard reaction can proceed via recombination of acetaldehyde and glycolaldehyde originating from both sugars and specific amino acids (e.g., serine, α‐alanine, and threonine) under pressure cooking conditions (121°C, 25 min, pH = 7) (Limacher et al., 2008). The Maillard reaction is reportedly a major source of furan in many model systems and actual foods (Senyuva & Gökmen, 2007; Bi et al., 2017; Guo et al., 2019; Kim et al., 2015).…”
Section: Formation Pathways Of Furan In Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids, particularly serine and cysteine derivatives, can facilitate furan formation. Additionally, the decomposition of unsaturated fatty acids, specifically 4-hydroxy-2-alkenals, can serve as precursors for furan compound formation (Guo et al, 2019).…”
Section: Profiling Bioflavor Compoundmentioning
confidence: 99%